Consumer Acceptance of Insects as Food: Revision of Food Neophobia Scales. Issue 3 (27th May 2022) - Gómez-Luciano, Cristino A.; Rondón Domínguez, Félix R.; Vriesekoop, Frank; Urbano, Beatriz
Abstract: This study aimed to get insight into the acceptance of insects as food using neophobia descriptors. Data were collected through questionnaires applied to a Spanish-Dominican sample. Models were created using binary logistic regression, and determinants of acceptance of insects as food were obtained. The results reveal that Dominicans presented the highest food neophobia and the lowest acceptance of insects as food. The openness to eat almost anything is the positive determinant in Spain for accepting insects as food, while in the Dominican Republic to overstate the benefits of the new food technologies. Principal component analysis was used to calculate the optimal number of descriptors in the neophobia scales; 3–5 descriptors could be removed. Marketers can use these results to better understand how to market insect-based products considering different contexts.